Evidence of Reduced CBG Cleavage in Abdominal Obesity: A Potential Factor in Development of the Metabolic Syndrome - Nenke, M. A.; Lewis, J. G.; Rankin, W.; Torpy, D. J (Hormone and Metabolic Research, 2016)
Corticosteroid-binding globulin (CBG) is involved in the regulation of cortisol delivery. Neutrophil elastase-mediated cleavage of high to low affinity CBG (haCBG to laCBG) induces cortisol release at inflammatory sites. Past studies have shown reduced CBG in obesity, an inflammatory state, particularly in central adiposity/metabolic syndrome. We performed an observational, cross-sectional study of the effects of obesity, age and sex on ha/laCBG in 100 healthy volunteers. Total and haCBG levels were 11% higher in women but did not vary with age or menopausal status. Total CBG levels were lower with increased body weight and waist circumference; laCBG levels were lower with increased body weight, waist circumference, body mass index and body fat; higher haCBG levels were seen with increased body fat. The relation between CBG and adiposity appeared to be driven predominantly by the metabolic syndrome group. The results suggest reduced CBG cleavage in central obesity, possibly contributing to the characteristic inflammatory phenotype of the central obesity and metabolic syndrome. The mechanism of gender differences in CBG levels is unclear.
Keywords: cortisol; high-affinity CBG; low-affinity CBG; inflammation